Numerical Simulations of Combined Brine Flooding With Electrical Heating–Assisted Depressurization for Exploitation of Natural Gas Hydrate in the Shenhu Area of the South China Sea - Zhang, Qi; Wang, Yanfei (Frontiers in Earth Science, 2022)
The Shenhu area of the South China Sea (SCS) is one of the most promising fields for natural gas hydrate (NGH) exploitation. However, previous studies conclude that using only depressurization is inefficient for this challenging hydrate deposits surrounded by permeable water zones, which requires assistance by thermal stimulation to promote hydrate decomposition and methane recovery. However, traditional thermal stimulation methods with hot water or steam injection induce massive heat loss along the wellbore. In addition, in situ electrical heating only results in a limited high temperature region due to low thermal conductivity of hydrate deposits. Therefore, we numerically investigate the performance of combined brine flooding with electrical heating–assisted depressurization in horizontal wells for exploitation of natural gas hydrate in the SCS, which simultaneously possesses the merits of low heat loss and enhanced heat transfer by convection. Our simulation results show that thermal stimulation by combined brine flooding with electrical heating can significantly enhance hydrate dissociation and methane recovery. After 20 years of production, the cumulative methane production of combined brine flooding with electrical heating–assisted depressurization is 1.41 times of that conducted by the only depressurization method. Moreover, the energy efficiency can be improved by reducing electrical heating time, and terminating electrical heating with 70% hydrate dissociation achieves the highest net energy gain. In addition, methane recovery and net energy gain increases with electrical heating power and brine injection pressure but with a decreasing rate. Therefore, the selection of electrical heating power and brine injection pressure should be performed carefully and comprehensively considering both the efficiency of gas production and risks of geological hazard. It is hoped that our research results will provide reference and guidance for the development of a similar NGH reservoir in order to promote the industrial development process of NGH.